Reassessing Britain's 'Post-war consensus': the politics of reason 1945–1979. Issue 2 (12th June 2018) - Blackburn, Dean
Abstract Since the late-1970s, scholars have been engaged in a vibrant debate about the nature of post-war British politics. While some writers have suggested that the three decades that succeeded the Second World War witnessed a bi-partisan consensus on key policy questions, others have argued that it was conflict, not agreement, that marked the period. This article offers a novel contribution to this controversy by drawing attention to the epistemological beliefs of the Labour and Conservative parties. It argues that once these beliefs are considered, it becomes possible to reconcile some of the competing claims made by proponents and critics of the 'post-war consensus' thesis. Labour and Conservative leaders may have been wedded to different beliefs, but they also shared a common enthusiasm for empiricist reasoning and were both reluctant to identify fixed political 'ends' that they sought to realise. Consequently, they were both committed to evolutionary forms of change, and they eschewed the notion that any social or political arrangement was of universal value.